(untitled) (Baghdad Science Journal, 2023)
The topological parameters of the metal-metal and metal-ligand bonding interactions in a trinuclear tetrahydrido cluster [(Cp*Co) (CpRu)2 (μ3-H) (μ-H)3]1 (Cp* = η5 -C5Me4Et), (Cp = η5 -C5Me5), was explored by using the Quantum Theory of Atoms-in-Molecules (QTAIM). The properties of bond critical points such as the bond delocalization indices δ (A, B), the electron density ρ(r), the local kinetic energy density G(r), the Laplacian of the electron density ∇2ρ(r), the local energy density H(r), the local potential energy density V(r) and ellipticity ε(r) are compared with data from earlier organometallic system studies. A comparison of the topological processes of different atom-atom interactions has become possible thanks to these results. In the core of the heterometallic tetrahydrido cluster, the Ru2CoH4 part, the calculations show no existence of any bond critical points (BCP) or identical bond paths (BPs) between Ru-Ru and Ru-Co. Electron densities are determined by the position of bridging hydride atoms coordinated to Ru-Ru and Ru-Co, which significantly affects the bonds between these transition metal atoms. On the other hand, the results confirm that the cluster under study contains a 7c–11e bonding interaction delocalized over M3H4, as shown by the non-negligible delocalization index calculations. The small values for electron density ρ(b) above zero, together with the small values, again above zero, for Laplacian ∇2ρ(b) and the small positive values for total energy density H(b), are shown by the Ru-H and Co-H bonds in this cluster is typical for open-shell interactions. Also, the topological data for the bond interactions between Co and Ru metal atoms with the C atoms of the cyclopentadienyl Cp ring ligands are similar. They show properties very identical to open-shell interactions in the QTAIM classification.